Co-solvent enhanced zinc oxysulfide buffer layers in Kesterite copper zinc tin selenide solar cells1. Issue 23 (21st June 2015) - Steirer, K. Xerxes; Garris, Rebekah L.; Li, Jian V.; Dzara, Michael J.; Ndione, Paul F.; Ramanathan, Kannan; Repins, Ingrid; Teeter, Glenn; Perkins, Craig L.
<x xml:space="preserve">Abstract</x> Performance deficiencies from the too large conduction band offset between Cu2ZnSnSe4/ZnOS heterojunctions are abated by the inclusion of a co-solvent during aqueous growth of the buffer layer.